Identifikasi Kadar Gula Darah pada Masyarakat Pesisir Kelurahan Kasilampe - Irma Yunawati; Wa Ode Salma; Nurnashriana Jufri; Rahayanah Rahayanah; Sinar Dwi Ulfa; Citra Nurhalizah Pini; Lisnawati Lisnawati; Idham Mahmud; Nurnita Nurnita; Nabil Al Mahmud (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Diabetes Mellitus is a medical condition usually characterized by blood glucose levels that exceed normal limits. Glucose in the blood comes from carbohydrates consumed through food, which are then stored as glycogen in the liver and skeletal muscles. Diabetes mellitus has a serious impact as the main cause of chronic complications, including coronary heart disease and stroke which accounts for 65% of deaths. Other complications, such as retinopathy and diabetic foot, are major causes of disability. Overall, these complications increase mortality, morbidity, disability, and the burden of medical costs. This article presents the results of research regarding blood glucose levels among the people of Kasilampe Village, Kendari City, Southeast Sulawesi. This activity involved 50 respondents consisting of 15 men (30%) and 35 women (70%). The aim of this research is to identify blood sugar levels and increase public understanding of the importance of carrying out regular health checks. The method used in this research is the accidental sampling method, namely by selecting individuals who are accessible and willing to take blood glucose level checks.The examination results showed that 35 respondents (70%) had blood glucose levels below 140 mg/dL, which indicates good glucose control. Based on the results of the examination, there were 7 respondents (14%) in the range of 140-199 mg/dL, which indicates that the respondent's glucose level was included in the pre-diabetes category and 8 respondents (16%) had glucose levels ≥ 200 mg/dL, which indicates that the The respondent's glucose is included in the Diabetes category. These findings emphasize the need for appropriate health interventions and education regarding healthy eating patterns to prevent diabetes mellitus. It is hoped that this activity can become the basis for a more effective diabetes prevention program in the community.